'There Was Never Really Any Question of Anything Else': Young People's Agency, Institutional Habitus and the Transition to Higher Education - Smyth, Emer; Banks, Joanne (My University, 2012)
International research into educational decision-making has been extensive, focusing on the way in which young people and their families assess the different options open to them. However, to what extent can we assume that different groups of young people have equal access to the information needed to make such an assessment? And what role, if any, do schools play in this process? Using in-depth qualitative interviews from two schools with very different student intakes, this paper examines the key influences which shape young people?s choices. Decisions about whether to go on to higher education are found to reflect three sets of processes: individual habitus; the institutional habitus of the school, as reflected in the amount and type of guidance provided; and young people?s own agency, namely, the conscious process whereby students seek out information on different options and evaluate these alternatives.
PUBLISHED
Keywords: agency; education; higher education; Inclusive Society